2009
DOI: 10.21273/hortsci.44.5.1330
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Methyl Jasmonate as a Harvest Aid for ‘Thompson Seedless’ Grapes: Concentration and Time Needed for Consistent Berry Loosening

Abstract: The application of methyl jasmonate (MeJA) to grapes (Vitis vinifera L.) may decrease fruit detachment force (FDF) and promote the development of dry stem scars on the berries, both of which could improve the quality of machine-harvested raisin grapes. However, treatment with MeJA also promotes preharvest fruit drop, which is undesirable. Thus, experiments were conducted to determine how the concentration of MeJA applied and time after treatment affect FDF and abscission of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…applications were effective in reducing FDF and inducing fruit abscission at a concentration of 10 mM and higher (Hartmond et al, 2000;Kender et al, 2001). Also, in grapes, MeJa was effective in inducing fruit drop at a concentration of 10 to 20 mM (Fidelibus et al, 2007), although lower rates of application (between 2 and 10 mM) were subsequently found to be better suited for mechanical harvesting applications (Gonzalez-Herranz et al, 2009). In blueberry, it may be expected that the fruit drop responses reported here would be reproducible under conditions of mechanical harvesting.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…applications were effective in reducing FDF and inducing fruit abscission at a concentration of 10 mM and higher (Hartmond et al, 2000;Kender et al, 2001). Also, in grapes, MeJa was effective in inducing fruit drop at a concentration of 10 to 20 mM (Fidelibus et al, 2007), although lower rates of application (between 2 and 10 mM) were subsequently found to be better suited for mechanical harvesting applications (Gonzalez-Herranz et al, 2009). In blueberry, it may be expected that the fruit drop responses reported here would be reproducible under conditions of mechanical harvesting.…”
Section: Discussionmentioning
confidence: 96%
“…The application of MeJa, alone and in combination with other abscission agents, resulted in fruit abscission in sweet orange (Hartmond et al, 2000;Kender et al, 2001). Methyl jasmonate was also effective in reducing FDF and inducing fruit abscission in grapes (Fidelibus et al, 2007;Gonzalez-Herranz et al, 2009). Additionally, coronatine, a naturally produced compound with functional properties similar to the jasmonates, induced fruit abscission in citrus (Burns et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl jasmonate might be a useful abscission agent in citrus , but its efficacy seems to be lower than ethylene releasing compounds as ethephon in other plants (BURNS et al, 2008). FIDELIBUS et al (2007) and GONZÁLEZ-HERRÁNZ et al (2009) have shown that methyl jasmonate selectively induces abscission of mature grape berries and promotes dry stem scars on the abscission zone, demonstrating that these effects are dose dependant.…”
Section: Iii3 Introductionmentioning
confidence: 99%
“…When the clusters cotreated with methyl jasmonate (20 and 40 mmol•L -1 ) and ethephon (1000 mg•L -1 ) were shaken by hand at harvest, the percentages of detached berries presenting scar tissue in the abscission zone were greater than 50 %(Fig. III.2) GONZÁLEZ-HERRÁNZ et al (2009). in cv.…”
mentioning
confidence: 98%